2021
DOI: 10.1371/journal.pone.0247679
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, stress, fear and social support during COVID-19 pandemic among Jordanian healthcare workers

Abstract: The emergence of Coronavirus disease 2019 (COVID-19) has affected health-care workers’ psychological and mental health. Few studies have been conducted examining the psychological effect of COVID-19 on health-care worker psychological health in Jordan. Therefore, the present study aims to assess the respective levels of fear, anxiety, depression, stress, social support, and the associated factors, experienced by Jordanian health-care workers during the COVID-19 Pandemic. This study adopted a cross-sectional, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
273
8
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(372 citation statements)
references
References 37 publications
27
273
8
11
Order By: Relevance
“…In addition, frontline healthcare workers engaged direct care of patients were significantly associated with higher symptoms of psychological distress (depression, anxiety and insomnia) (19). In contrast, preliminary data in Jordan indicated that being male, married, age 40 and above and have more clinical experience are associated with the psychological distress of healthcare providers (28). These factors have also been linked during the previous outbreak (SARS) in which high levels of depressive symptoms were observed among healthcare workers who closely treat patients (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, frontline healthcare workers engaged direct care of patients were significantly associated with higher symptoms of psychological distress (depression, anxiety and insomnia) (19). In contrast, preliminary data in Jordan indicated that being male, married, age 40 and above and have more clinical experience are associated with the psychological distress of healthcare providers (28). These factors have also been linked during the previous outbreak (SARS) in which high levels of depressive symptoms were observed among healthcare workers who closely treat patients (12).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding GAD-7 anxiety, 15-21 was considered with severe anxiety, 0-4 (normal), 5-9 (mild), and 10-14 having moderate anxiety. The 7-item Insomnia Severity Index (ISI; range, 0-28) was used to assess and categorized ISI, normal (0-7), subthreshold (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21), and severe (22)(23)(24)(25)(26)(27)(28) insomnia (22). The last part of the questionnaire was the 22-item Impact of Event Scale -Revised (IES-R; range, 0-88) and will be recorded as normal (0-8), mild (9-25), moderate (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), and severe (44-88) distress (23).…”
Section: Instrumentsmentioning
confidence: 99%
“…The global employment situation of health workers caused by the COVID-19 pandemic requires a lot of attention and concentration, high responsibility, work overload, and long or disorderly hours and shifts; which puts job performance and its health, social and economic repercussions at risk. The pandemic has affected health-care workers’ psychological and mental health [ 1 ]. This situation implies special attention to the human side of management.…”
Section: Introductionmentioning
confidence: 99%
“…15) In the United States, HCPs are at an increased risk for mental illnesses such as depression, anxiety, burnout, and insomnia, which have further increased under the stressful circumstances of COVID-19 due to isolation, reduced income, and risk of infection. 16) Although 70% of HCPs engaged in COVID-19 care are females, 17) medical care has been affected by the largescale retirement of nurses after the pandemic in some hospitals in Japan. 7) In a 2020 tentative report by the Police Agency in Japan, the rate of suicides was much higher than the number of deaths caused by COVID-19, and the prevalence among females has increased 80% more than that prior to the pandemic.…”
Section: Issues Encountered By Physicians During the Covid-19 Pandemicmentioning
confidence: 99%